Pembuatan Website Pariwisata Tentang Relief Candi Bahal I di Padang Lawas Utara - Felix Khalasnikov Napitupulu (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
Indonesia is an archipelago and is therefore referred to as Nusantara (nusa means island and antara means beyond or outside). There are about 17,024 islands separated by sea. Its people consist of 1,340 ethnic groups divided into 300 ethnic groups representing different cultures. This diversity has resulted in 1,728 intangible cultural heritages and more than 700 languages. North Sumatra has scenic beauty in tourism both in nature such as the splendor of Lake Toba and in man-made attractions such as Maimun Palace and Medan Grand Mosque. However, North Sumatra has archaeological sites whose existence is less well known both by the people of North Sumatra and the outside world. This gave rise to the idea of developing a media website to publicize archaeological sites in North Sumatra, especially Bahal I Temple. The questionnaire was distributed in class B 2021 German class of Medan State University. Based on the questionnaire, 83.9% of the respondents were not familiar with Bahal I Temple. Further results showed that 54.8% of the respondents had no knowledge about the reliefs in Bahal I Temple, 80.6% did not know its meaning, and 80.6% also did not know Wixsite media. This research method is a development research. This research uses the ADDIE model which consists of 5 stages: 1) Analysis; 2) Design; 3) Development; 4) Implementation; 5) Evaluation. The data sources for this research are journals and experts. The result of this research is a cultural website about the reliefs of Bahal I Temple